Status of Coral Reefs in The Waters of Tidung Island Kepulauan Seribu DKI Jakarta Province Based on Underwater Photo Transect Analysis - Fauzanabri, Renno; Manembu, Indri Shelovita; Schaduw, Joshian Nicolas William; Manengkey, Hermanto W. K; Sinjal, Chatrien A. L; Ngangi, Edwin L. A (Jurnal Ilmiah Platax, 2021)
Tidung Island is one of the islands as well as a village located in the district of South Kepulauan Seribu. The purpose of this research is to measure the environmental parameters of the waters, provide information on the condition of coral reefs, and know the form of coral growth that dominates Tidung Island. Data retrieval is done using UPT (Underwater Photo Transect) method at a depth of 5 meters at three different stations. For the processing of data that has been taken, the photo results in the form of coral cover are entered into Coral point count with excel extensions (CPCe) 4.1 application and analyzed. The results of the analysis will be stored on the storage device, then the results will be ready to be opened in Excel format. The results of this research show that the environmental parameters of the waters include, including temperature, degree of acidity, and salinity, have a range of values that are still suitable for the growth and development of corals, however, the brightness level in these waters is relatively low. The condition of coral reefs in stations 1 and 3 are in the category of damage, with hard coral cover values of 24.67% and 11.00%, while at station 2 coral reef conditions are in the good category with a hard coral cover value of 56.27%. Based on the assessment, obtained an average value of the percentage of hard corals by 30.65%, this indicates that the condition of coral reefs in Tidung Island is in the moderate category. The low percentage of hard corals is caused by the high component of dead corals with algae and rubble. Based on the results of this research, a known form of coral growth that dominates the waters of Tidung Island is foliose coral.Keywords: Domination; CPCe; Tidung Island; Coral Reef; UPT.AbstrakPulau Tidung merupakan salah satu pulau sekaligus kelurahan yang terletak di wilayah Kecamatan Kepulauan Seribu Selatan. Tujuan dari penelitian ini adalah mengukur parameter lingkungan perairan, menyediakan data informasi kondisi terumbu karang, dan mengetahui bentuk pertumbuhan karang yang mendominasi di Pulau Tidung. Pengambilan data dilakukan dengan menggunakan metode UPT (Underwater Photo Transect) atau Transek Foto Bawah Air pada kedalaman 5 meter di tiga stasiun berbeda. Untuk pengolahan data yang sudah diambil, hasil foto berupa tutupan karang di input ke dalam aplikasi Coral point count with excel extensions (CPCe) 4.1 dan dianalisis. Hasil analisis akan tersimpan di perangkat penyimpanan, yang kemudian hasilnya akan siap untuk dibuka dalam format Excel. Hasil dari penelitian ini menunjukkan bahwa parameter lingkungan perairan meliputi, suhu, derajat keasaman, dan salinitas, memiliki kisaran nilai yang masih sesuai untuk pertumbuhan dan perkembangan karang, namun tingkat kecerahan pada perairan ini relatif rendah. Kondisi terumbu karang pada stasiun 1 dan 3 berada pada kategori buruk dengan nilai tutupan karang keras sebesar 24,67% dan 11,00%, sedangkan pada stasiun 2 kondisi terumbu karang berada pada kategori baik dengan nilai tutupan karang keras sebesar 56,27%. Berdasarkan penilaian tersebut, diperoleh nilai rata-rata persentase karang keras sebesar 30,65%, hal ini menunjukkan bahwa kondisi terumbu karang di Pulau Tidung berada pada kategori sedang. Rendahnya persentase karang keras disebabkan tingginya komponen karang mati oleh algae dan patahan karang. Berdasarkan hasil penelitian ini diketahui bentuk pertumbuhan karang yang mendominasi perairan Pulau Tidung adalah coral foliose.Kata kunci: Dominasi; CPCe; Pulau Tidung; Terumbu Karang; UPT